Health group walks: making sense of associations with the natural landscape. Issue 1 (2nd January 2022) - Grant, Gordon; Pollard, Nick
ABSTRACT: Literature about health group walks typically focuses on explaining health and wellbeing outcomes. Less attention has been paid to how encounters with the natural landscape are experienced during these walks. This paper is based on an ethnographic study of a health walk group in a rural area of the UK that encapsulated health, social and environmental connections. It examines how walkers describe and make sense of their connections with natural landscapes. Mobility practices and contingent factors are found to mediate walkers' exposure to and experience of the natural landscape. Theories underpinning connections with the natural landscape and place are used to review the findings. Implications for health walks and further research are considered.